Abnormal B-Cell Maturation and Increased Transitional B Cells in CBL Syndrome - Saettini, Francesco; Coliva, Tiziana Angela; Vendemini, Francesca; Galbiati, Marta; Bugarin, Cristina; Masetti, Riccardo; Moratto, Daniele; Chiarini, Marco; Guerra, Fabiola; Iascone, Maria; Badolato, Raffaele; Cazzaniga, Giovanni; et al. (Frontiers in Pediatrics, 2022)
CBL syndrome is a Noonan-like RASopathy with heterogeneous clinical phenotype and predisposition to juvenile myelomonocytic leukemia (JMML). Here we describe two patients with identical germline CBL mutation and clinical and immune-hematological overlapping features with Autoimmune Lymphoproliferative Syndrome (ALPS) and B cell expansion with NF-κB and T cell Anergy (BENTA) syndrome. Increased immature/transitional B cells can be depicted in CBL syndrome, ALPS, and BENTA. Nonetheless, our patients here described showed peculiar B-cell phenotype due to increased immature/transitional CD34+ B cells. This feature differentiates CBL syndrome from BENTA, pointing toward an abnormal proliferation of B cell early precursors.